Advancing Innovation in the Republic of Tatarstan : A Framework for Competing and Thriving in the Global Economy - World Bank (Washington, DC, 2013)
This report provides recommendations for transforming Tartarstan's traditional industrial economy into a globally competitive, knowledge based economy, and for involving Russia in the development process. A broad range of innovation policies are best handled at the regional level and are difficult to achieve through an approach solely based on national innovation. Regional innovation systems are constantly evolving and government must be flexible enough to support learning and interactions between innovation stakeholders and the ability of firms to find their competitive advantages in global markets.